Mapping a Revolutionary Lexicon: Semantic Networks and the Ideological Architecture of People’s Multiparty Democracy in Nepal - Karki, Mrigendra Bahadur (State, Society and Development: PMPD Perspectives, 2025)
This article explores the ideological architecture of People’s Multiparty Democracy (PMPD) as articulated by Madan Bhandari and institutionalized by the Communist Party of Nepal (Unified Marxist–Leninist). The study aims to examine how PMPD constructs a revolutionary framework that synthesizes Marxist principles with democratic pluralism, ethical leadership, and institutional accountability. It specifically highlights the ways that the PMPD’s conceptual discourse organizes and communicates a coherent vision of socialist transformation in Nepal. Using co-occurrence network analysis, implemented in RStudio and visualized through igraph and ggraph, the research maps the relational logic and semantic layering across Bhandari’s collected writings. Three core conceptual clusters emerge: (1) Party–Revolution–Leadership, (2) Democracy–Multiparty–System–People, and (3) Principle–Ideology–Unity. Together, they constitute a structured lexicon that articulates PMPD’s political imagination and strategic coherence. The study demonstrates how PMPD’s discourse mediates between foundational Marxist commitments and evolving democratic realities, presenting a model of ideological transformation rooted in the context of Nepal. By combining computational methods with critical discourse analysis, this article contributes to scholarship on indigenous Marxist formations and offers a methodological intervention for studying socialist theory in transitional societies.